Mlčení je forma komunikace. Feministické debaty o politických aspektech psychologické praxe - Kateřina Machovcová (Gender a Výzkum)
The heated debate between feminism(s) and psychology(ies) about being political goes beyond the understanding of feminism as a dangerous ideology that needs to be divorced from the respect for approaches intrinsic to psychological practices. Political activism is frequently understood as a core feminist value, but different ethics can come into play in psychology and psychotherapy. Professionals engaged in critical and feminist approaches seek to combine being political while cherishing the autonomous decision-making of each and every client. However, we also encounter positions where individual work is rejected and only collective activism is to be pursued, or on the other hand, positions where activism beyond individual help is deemed unrealistic. In the following text different perspectives on feminist politics and psychology will be presented. For instance, critical psychology can serve as one of the platforms where feminisms and the critique of psychological theories can come together in claiming that neutrality is impossible. The theoretical part of the article is illustrated with examples, some of which were drawn from the empirical material collected for the author’s dissertation project ‘Gendering Psychological Counselling’.